Dynamic Response of Pavement Plates to the Positive and Negative Phases of the Friedlander Load - Alisjahbana, S.W.; Safrilah; Putra, J.C.P.; Asmi, A.; Alisjahbana, I.; Kiryu, S.; Gan, B.S. (Проблемы прочности, 2018)
The dynamic response of pavement plates to a localized Friedlander load based on the threeparameter foundation model with the account of soil inertia is analyzed. Выполнен анализ динамической реакции мостовых плит на локализованную нагрузку Фридлендера на базе трехпараметрической модели основы с учетом инерции грунта.